2005
DOI: 10.1021/jm049050v
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Docking, QM/MM Methods, and MD Simulation for Binding Affinity Estimation of Metalloprotein Ligands

Abstract: To alleviate the problems in the receptor-based design of metalloprotein ligands due to inadequacies in the force-field description of coordination bonds, a four-tier approach was devised. Representative ligand-metalloprotein interaction energies are obtained by subsequent application of (1) docking with metal-binding-guided selection of modes; (2) optimization of the ligand-metalloprotein complex geometry by combined quantum mechanics and molecular mechanics (QM/MM) methods; (3) conformational sampling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 101 publications
0
128
0
Order By: Relevance
“…Conformational sampling using 200-ps MD simulations did not improve the statistics significantly (r 2 = 0.589). We showed previously [18,32] that these correlations can be amended by a careful selection of the used intervals of MD simulations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conformational sampling using 200-ps MD simulations did not improve the statistics significantly (r 2 = 0.589). We showed previously [18,32] that these correlations can be amended by a careful selection of the used intervals of MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The QM/MM optimization of the best FlexX poses showed that the hydroxamate groups of all 28 derivatives created, along with the histidine triad of MMP-9, rather similar trigonal bipyramidal coordination spheres around the catalytic zinc [18] (Figure 1). Glu402 formed the hydrogen bonds with the nonionized hydroxyl group of the hydroxamates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations